Desenvolvimento de nanocápsulas poliméricas para liberação pulmonar do dipropionato de beclometasona - Chassot, Janaíne Micheli (2013)
Polymeric nanocapsules have been studied extensively for drug delivery by various routes of administration. Currently, the nanoencapsulation of drugs is considered the most efficient means of ensuring controlled release, specific targeting and reduction of adverse effects. In this context, the aim of this work was to develop polymeric nanocapsules for pulmonary delivery of beclomethasone dipropionate (BD). Nanocapsules have been prepared from 2 polymers, poly(-caprolactone) (PCL) and ethyl cellulose (EC). To quantify the drug in the nanostructures, the analytical method was developed and validated. This method showed to be specific, linear, precise, accurate and robust. Nanocapsules were prepared by interfacial deposition of preformed polymers and were evaluated as to pH, particle diameter, polydispersity index, drug content, encapsulation efficiency and zeta potential. All samples showed encapsulation efficiency greater than 98%, negative zeta potential, pH value in the range of neutrality and drug contents close to their theoretical values. The size distribution was nanometric (158-270 nm) with polydispersity index lower than 0.2. The results of the photodegradation study showed that polymeric nanocapsules were able to protect BD from UVC radiation when compared to the free drug solution. In vitro release experiments were performed using the dialysis bag technique, which showed, for all formulations, a prolonged drug release mediated by anomalous transport and first order kinetics. Free drug in solution took between 24 and 36 h to reach 100% of release, whereas nanocapsules were able to control the drug release for up to 108 h, depending on the polymer employed. Nanocapsules of EC and PCL were evaluated for in vitro and in vivo toxicity and the results suggest that the proposed formulations are safe. In the final stage of the work, pullulan was proposed as stabilizer agent for PCL nanocapsules and the results obtained for the zeta potential and the drug content suggested that these formulations have become more stable. Thus, the nanocapsules developed in this work represent a promising alternative for the pulmonary delivery of BD in the treatment of asthma and other respiratory disorders.